Introduction: the ecology of subsistence / James Parson J. - Parsons, James J.
Introduction, the ecology of subsistence; fieldwork on the Miskito coast; expansion and change; the economics of production and distribution; population and society; subsistence strategy, regulation, and capacity; rain, wind, land, and water; food preparation and consumption; previous research on the Miskito coast; the availability of Miskito food resources; previous research on the Miskito coast; the availability of Miskito food resources.